2011
DOI: 10.4274/tpa.358.1338
|View full text |Cite
|
Sign up to set email alerts
|

Çocuk ve ergenlerde Hashimoto tiroiditi: klinik ve laboratuvar bulgularının değerlendirilmesi

Abstract: Aim:The objective of this study was retrospective analysis of clinical and laboratory findings of children and adolescents with Hashimoto thyroiditis. Material and Method:We evaluated 78 patients with HT who were between 4-17 years of age. Physical examination and family history of the patients, thyroid functions, auto-antibody titers and USG scans were evaluated retrospectively. Results: Two (2.6%) patients presented with hyperthyroidism, while 10 (11.7%), 17 (21.8%) and 49 (62.8%) patients presented with hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(39 reference statements)
0
5
0
1
Order By: Relevance
“…Consistent with our study, Tuhan et al (15) found that there was no difference in terms of gender, adolescence and presence of goiter between the groups that were compared according to thyroid function status. Dündar et al (13) reported a higher rate of goiter in euthyroid cases.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Consistent with our study, Tuhan et al (15) found that there was no difference in terms of gender, adolescence and presence of goiter between the groups that were compared according to thyroid function status. Dündar et al (13) reported a higher rate of goiter in euthyroid cases.…”
Section: Discussionmentioning
confidence: 96%
“…Euthyroidism is the most common thyroid pattern associated with Hashimoto's thyroiditis (20-80%). Dundar et al (13) reported euthyroidism in 62.8% of children and adolescents with Hashimoto's thyroiditis, Özen et al (14) and Tuhan et al (15) reported euthyroidism in 51.2% and 36.7% of these cases, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Hashimoto tiroiditinin sıklığı özellikle ergenlik döneminde artış göstermekte, 4 yaş altında ise oldukça nadir görülmektedir (29,30) . Bu çalışmada da Hashimoto tiroiditli hastaların %78'i pubertaldi ve ortanca yaşları literatürle uyumlu olarak 13,8 (10,(8)(9)(10)(11)(12)(13)(14)(15) yıldı.…”
Section: Discussionunclassified